Analysis of the Utilization of Platform Merdeka Mengajar (PMM) to Improve Teacher Professionalism at SDN Sidoklumpuk Sidoarjo: Analisis Pemanfaatan Platform Merdeka Mengajar (PMM) Untuk Meningkatan Profesionalisme Guru di SDN Sidoklumpuk Sidoarjo - Setyawati, Reny Hajar; Hisayatullah (Indonesian Journal of Innovation Studies, 2026)
General Background: Teacher professionalism requires continuous development in pedagogical, professional, reflective, and digital competencies. Specific Background: Platform Merdeka Mengajar (PMM) provides Pelatihan Mandiri, Perangkat Ajar, and Video Inspirasi to support teachers implementing the Merdeka Curriculum at SDN Sidoklumpuk Sidoarjo. Knowledge Gap: Previous studies reported benefits of PMM for teacher competencies, while this study examines its utilization across five professionalism indicators in a specific elementary-school context. Aims: This study analyzes PMM utilization and its contribution to teacher professionalism. Results: A qualitative case study using interviews, observation, and documentation found stronger material mastery, curriculum understanding, teaching creativity, reflective-evaluative practice, digital technology use, confidence, and collaboration, supported by school leadership and teacher collaboration. Novelty: The study highlights integrated digital assistance with the Merdeka Curriculum. Implications: PMM can serve as a flexible, contextual, and continuous medium for teacher professional development. Key Findings Highlights Independent training strengthens teachers’ material mastery and curriculum understanding. Inspirational content encourages creative and reflective teaching practices. School leadership and peer collaboration support sustained digital professional development. Keywords: Platform Merdeka Mengajar, Teacher Professionalism, Merdeka Curriculum, Professional Development, Digital Transformation